Perancangan Aplikasi Layanan Pengaduan Kerusakan Jalan Berbasis Android - Falasyfa, Rizky Samudra; Avianto, Donny (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The android-based road damage complaint service application is a technological innovation that aims to improve the reporting and management of road damage. In the era of digitalization, people expect a lot from public services, especially infrastructure. However, the reporting process is still often done manually, causing weaknesses such as data loss, slow response and ineffectiveness. This application is an effective solution to overcome these problems. Users can easily report road damage through their Android devices. The benefit of this application is the ability to know the level of road damage in each report, making it easier for the authorities to determine the priority of handling. In addition, the app allows users to provide a detailed description of the damage, upload photos as evidence, and add additional relevant information. The app provides a complete and easy-to-fill form, making the reporting process more efficient.Once the report is submitted, users will receive a confirmation of report receipt to track the status of the report. The relevant agencies will utilize the app as a tool to manage incoming complaints, promptly responding to reports and processing them based on the priority and type of damage reported. Therefore, this application brings significant changes by improving public services and ensuring better infrastructure maintenance.